Character Formation Through Meaningful Relationships in Learning Interactions at Islamic Higher Education - Sukirman Sukirman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aims to describe the use of language features in relation to meaning in the form of antonyms, synonyms, and hyponyms in teaching interactions at IAIN Palopo. The research was conducted using a descriptive qualitative approach that uses data sources from narratives or interactions that take place in learning. The data is from words and phrases containing meaningful relationships obtained using a recording instrument (Handycam). Then, the data is classified and analyzed using description, interpretation, and explanation techniques. The study results show that the language features of meaning relations used in teaching interactions at IAIN Palopo are represented as antonyms, synonyms, and hyponyms. Each type of meaning relation shows the meaning of euphemization aspects, sensory aspects, experiential values, relational values, and expressive values. Furthermore, each aspect generally aims to express ideas through meaningful characters that affirm, explain, and convince the object of study to achieve competence..